LANGUAGE ANXIETY IN ENGLISH SPEAKING | CLASS - Nyayu Sugiharti, - (2007)
The phenomenon ofanxiety in speaking has been recognized in language learning for years. Students' behaviors like that of feeling embarrassed or fear to speak, stage fright, nervousness or panic were often reflected in their poor achievement. This situation indeed needs a notice. Due to this case, this research is aimed at investigating the nature ofanxiety in speaking class. It deals with the levels, types and causes ofanxiety and also language learning strategies in dealing with anxiety employed by the students. The method used in conducting this research is descriptive. The research involves 23 students ofEnglish Department ofUPI Bandung taking Speaking for General Communication. In collecting the data, this research employs Foreign Language Anxiety Scale of Horwitz and interview as the main instruments and class observation. Causes ofanxiety suggested by Young and language learning strategies suggested by Oxford are used as the frameworks of discussion. The results show that students' anxiety level is mildly anxious. It indicates students' readiness in facing problems in speaking class especially anxiety. It reveals that Communication Apprehension is the type mostly occurs, personality components are the major causes of anxiety and affective strategies are frequently employed by the students. It can be concluded that 1) students are ready to take speaking class; 2) students are uncomfortable in speaking class; and 3) personality components can be the major causes of anxiety and also the strategies in encountering anxiety. And then following can be recommended to lower students' anxiety level: 1) employing affective strategies; and 2) using challenging and motivating learning